Relation between baseline CXCR1 expression and neoadjuvant chemotherapy response in breast cancer patients - Sara Adel Amin; Emad Abd El Mongy Sadaka; Khalid Ahmed Ismail; Ashraf Fathy Barakat; Ahmed Abdel Aziem Menaisy; Amr Abd Elmoneim Mahmoud (Journal of the Pakistan Medical Association, 2023)
Objective: To examine the C-X-C Motif Chemokine Receptor 1 expression in breast cancer tissues prior to neo-adjuvant chemotherapy, and its relationship to neo-adjuvant chemotherapy effectiveness and other prognostic variables. Method: The prospective study was conducted at Kafrelsheikh University Hospital, Egypt, from November 2018 to March 2021, and comprised patients with recent histopathologically proven breast cancer cases eligible for chemotherapy. Paraffin blocks of tumour specimens were stained by immunohistochemical stain using concentrating rabbit anti-human C-X-C Motif Chemokine Receptor 1 polyclonal antibody kits. C-X-C Motif Chemokine Receptor 1 expression was classified into low and high categories. Patients were followed for 2 years for treatment response, disease recurrence and mortality. Data was analysed using SPSS 25. Results: Of the 100 females with mean age 50.2±12.1 years, 52(52%) had their left side affected, while 48(48%) had their right side affected. There were 52(52%) cases with mean age 49.2±12.9 years having high C-X-C Motif Chemokine Receptor 1 expresssion, while 48(48%) with mean age 51.4±11.2 years had low expression. There was a significant association between high expression and advanced tumour grade, advanced tumour stage, higher frequency of triple negative breast cancer and higher frequency of Ki-67-positive cancers (p<0.05). Patients with high C-X-C Motif Chemokine Receptor 1 expression had significantly lower frequency of complete pathological response when compared with patients with low expression (p<0.001). Patients with high expression had higher frequency of recurrence, shorter disease-free survival, higher mortality and shorter overall survival, but the difference was not significant (p>0.05). Multivariate logistic regression analysis identified triple negative hormonal status (p=0.031) and high baseline C-X-C Motif Chemokine Receptor 1 expression (p<0.001) as significant predictors of complete pathological response. Conclusions: There was found to be a link between baseline C-X-C Motif Chemokine Receptor 1 expression in breast cancer tissues and pathological response to neoadjuvant therapy in breast cancer patients. Keywords: Neoadjuvant therapy, Prognosis, Ki67 proliferation marker, Paraffin, Immunohistochemistry, Breast neoplasms, Chemokines.